Map location of the gene for a 130,000-dalton glycoprotein of bovine herpesvirus 1. - Lawrence, W C (1986)
A bovine herpesvirus 1 variant (mar6) containing a mutation in a viral glycoprotein with a molecular weight of 130,000 (g130) was isolated by selecting for resistance to a neutralizing monoclonal antibody (130-6) directed against g130. Mar6 was completely resistant to neutralization by monoclonal antibody 130-6 in the presence and absence of complement, but was neutralized by polyvalent immune sera. The mar6 mutant synthesized and processed g130, but produced plaques which failed to react with monoclonal antibody 130-6 in an in situ immunoassay (black plaque). However, monoclonal antibody 130-6 was capable of binding and immunoprecipitating g130 from infected-cell extracts produced by lysis of mar6-infected cells with nonionic detergents. The mutation in mar6 was mapped by marker rescue with cloned bovine herpesvirus 1 restriction enzyme fragments to a 3.8-kilobase fragment at approximate map units 0.405 to 0.432. In addition, it was found that a DNA probe containing the glycoprotein B gene of herpes simplex type 1 hybridized uniquely to the same 3.8-kilobase fragment which was shown by marker rescue to contain the mutation site in the gene for bovine herpesvirus 1 g130.